Automatic Estimation of Multidimensional Personality From a Single Sound-Symbolic Word - Sakamoto, Maki; Watanabe, Junji; Yamagata, Koichi (Frontiers in Psychology, 2021)
Researchers typically use the ‘big five’ traits as a standard way to describe personality, drawing from adjectival scales. The big five personality traits are evaluated in terms of extroversion, agreeableness, conscientiousness, neuroticism and openness. Personality evaluation is generally conducted using self-report questionnaires that require participants to respond to a large number of test items. This paper proposes an alternative method of estimating multidimensional personality traits from only a single word. We constructed a system that can convert a word that intuitively expresses personality traits into information expressed by 50 personality-related adjective pairs. This system can obtain information equivalent to the adjective scales using only a single word instead of asking many direct questions. To achieve this, we focused on onomatopoeia, a sound-symbolic word class in Japanese that involves the association between linguistic sounds and feelings. Sound-symbolic words can express diverse and complex aspects of personality traits. Using a single sound-symbolic word as input enables a more fine-grained analysis of personality than typical methods, and minimizes the burden on participants.